Estimation of Carbonate Elastic Properties from Nanoindentation Experiments to Reduce Uncertainties in Reservoir Modelling - De Paula, Osni; Pervukhina, M.; Gurevich, Boris; Lebedev, Maxim; Martyniuk, M.; Piane, C. (CSIRO Publishing, 2010)
Petrophysical properties of carbonate reservoirs, which are the majority of all hydrocarbon reservoirs worldwide, are much less predictable than the properties of siliciclastic reservoirs. This is mainly due to chemical interactions of carbonate rocks with percolating fluids that cause dissolution, ion exchange, and recrystallization in geological time. These processes result in dramatic changes in density, porosity, and permeability leadingto inhomogeneity of carbonate rocks on micro- and meso- scales. Quantification of the elastic variability of carbonate grains on the microscale is the first step to constrain models and to obtain more realistic predictions of practically important rock properties of carbonate reservoirs.In this study, we present elastic moduli of an oolite sample from the Dampier Formation - Pleistocene of Southern Carnarvon Basin, Western Australia, obtained by nanoindentation. Young’s moduli of this highly heterogeneous sample are measured at 49 points regularly distributed in a 70x70micrometer rectangular grid on the sample’s surface. The frequency diagram shows bimodal distribution of the Young’s moduli oriented around values of 56 GPa and 144 GPa that correspond to low and high density components of the grain respectively. These two solid phases are apparent in the high resolution scanning electron microscope images. We used the obtained moduli of this composite grain for numerical modelling using finite element approach of elastic properties of the carbonate sample from micro-Computed Tomography images. The results compare favourably with the elastic moduli obtained from acoustic velocities measured by ultrasonic technique.